Health-related quality of life in Brazilian community-dwelling and institutionalized elderly: Comparison between genders - CUCATO,GABRIEL GRIZZO (2016)
SUMMARY Objective To compare the health-related quality of life (HRQL) indicators between institutionalized and community-dwelling elderly men and women. Method This was a cross-sectional study with a sample of 496 elderly men and women, surveyed by researchers at a private hospital that attends institutionalized and community-dwelling elderly. HRQL (World Health Organization Quality of Life), daily living activities (Katz questionnaire), and instrumental daily living activities (Lawton questionnaire), mini-mental state examination, handgrip strength test, and function capacity (timed up and go test) were obtained. Results Institutionalized men presented higher scores in physical and psychological domains of HRQL compared to elderly men living alone (p<0.05). Among women, the scores in all domains (physical, psychological, relationship, and environment) were similar between institutionalized and community-dwelling individuals. Conclusion Institutionalized elderly men reported better scores in physical and psychological domains of HRQL compared to their community-dwelling pairs, while both institutionalized and community-dwelling elderly women presented similar HRQL.